Analyses related to the development of DSM-5 criteria for substance use related disorders: 2. Proposed DSM-5 criteria for alcohol, cannabis, cocaine and heroin disorders in 663 substance abuse patients - Hasin, Deborah S. (2011)
BACKGROUND: A number of changes have been proposed and investigated in the criteria for substance use disorders in DSM-5. However, although clinical utility of DSM-5 is a high priority, relatively little of the empirical evidence supporting the changes was obtained from samples of substance abuse patients. METHODS: Proposed changes were examined in 663 patients in treatment for substance use disorders, evaluated by experienced clinicians using the Psychiatric Research Interview for Substance and Mental Disorders (PRISM). Factor and item response theory analysis was used to investigate the dimensionality and psychometric properties of alcohol, cannabis, cocaine and heroin abuse and dependence criteria, and craving. RESULTS: The seven dependence criteria, three of the abuse criteria (hazardous use; social/interpersonal problems related to use; neglect of roles to use), and craving form a unidimensional latent trait for alcohol, cannabis, cocaine and heroin. Craving did not add significantly to the total information offered by the dependence criteria, but adding the three abuse criteria and craving together did significantly increase total information for the criteria sets associated with alcohol, cannabis and heroin. CONCLUSION: Among adult patients in treatment for substance disorders, the alcohol, cannabis, cocaine and heroin criteria for dependence, abuse (with the exception of legal problems), and craving measure a single underlying dimension. Results support the proposal to combine abuse and dependence into a single diagnosis in the DSM-5, omitting legal problems. Mixed support was provided for the addition of craving as a new criterion, warranting future studies of this important construct in substance use disorders.